An 8-bit CMOS dynamic voltage reference analog-to-digital converter - Li, Jingjing (2016)
In this project, an 8-bit asynchronous analog-to-digital converter (ADC) is introduced. The proposed ADC is designed to convert the continuous input signal ranging from 0 to 1V to 8 bits discrete output digital signal using 0.18 um CMOS technology.